2021
DOI: 10.3390/ijerph18168784
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Suicide Utility Perception on News over Terminally Ill Patients’ Suicide Attitudes: A Pilot Study

Abstract: Suicide represents a very important issue in public health. For approaching attitudes toward suicide, we have developed an instrument that, following previous recommendations, assesses specific thoughts related to the perception of suicide utility in the press. First of all, we will test the psychometric properties of the scale we created ad hoc for assessing suicide utility perception. After that, we expect to find that the suicide utility perception in the press will have a statistically significant impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Adicionalmente, los profesionales de enfermería han evidenciado su desacuerdo con la legitimación del suicidio, a pesar del contacto frecuente con pacientes con patología mental que podría conducirlos a adoptar una mejor actitud contrariamente a su mayor rechazo hacia las conductas suicidas (26,27). Otro tema que genera controversia es el suicidio en enfermos terminales, como lo descrito por García-Fernández et al, donde se informó que el 60 % de médicos están a favor del suicidio en este tipo de pacientes, lo que ameritaría investigaciones que permitan identificar diferencias, si es que se trata de manifestaciones de empatía o de opiniones fundamentadas (28). En este mismo sentido, una investigación realizada a estudiantes de Medicina y Psicología informó sobre actitudes más favorables hacia el suicidio en pacientes terminales (29).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Adicionalmente, los profesionales de enfermería han evidenciado su desacuerdo con la legitimación del suicidio, a pesar del contacto frecuente con pacientes con patología mental que podría conducirlos a adoptar una mejor actitud contrariamente a su mayor rechazo hacia las conductas suicidas (26,27). Otro tema que genera controversia es el suicidio en enfermos terminales, como lo descrito por García-Fernández et al, donde se informó que el 60 % de médicos están a favor del suicidio en este tipo de pacientes, lo que ameritaría investigaciones que permitan identificar diferencias, si es que se trata de manifestaciones de empatía o de opiniones fundamentadas (28). En este mismo sentido, una investigación realizada a estudiantes de Medicina y Psicología informó sobre actitudes más favorables hacia el suicidio en pacientes terminales (29).…”
Section: Discussionunclassified
“…Sin embargo, hay estudios que no encontraron diferencias significativas entre ambos grupos de profesionales, mientras que otros trabajos señalan actitudes más positivas respecto al suicidio, como los psiquiatras y enfermeros que laboran en áreas de salud mental, a diferencia de otros especialistas de las áreas de emergencia, por ejemplo (26,27). Al respecto, existe un predomino de actitudes de indiferencia para el suicidio en nuestro estudio, mientras que otros estudios señalan que una actitud más tolerante frente a la conducta suicida tiene una mayor relación con la ideación suicida y con la presencia de antecedentes de intentos de suicidio (28). Esta diferencia puede obedecer a que los médicos y los profesionales de la salud no suelen buscar ayuda especializada, ya sea por miedo a la crítica, temor a perder la licencia laboral, temas sociales, culturales, estigmas o predisposición a la autosuficiencia, lo que conlleva a la automedicación, generando un retraso en el acceso a la ayuda, incrementando el riesgo suicida (33,34).…”
Section: Discussionunclassified
“…It is fair that physicians offer their point of view on this topic, and these professionals must receive education on care’s legal, ethical, and social aspects. 27 - 29 It is important to motivate more authors to develop works in this sense and to know why doctors agree or disagree with euthanasia and assisted suicide to allow further reflection on the matter.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that in palliative care the sense of dignity was diminished by the loss of physical autonomy, 11,12,14,15,[20][21][22] the dependence and the vulnerability, 5,6,23,24 the loss of internal control over one's own body 25,26 and the loss of personal worth or values of life leading to loss of meaning in life. 6,27 Furthermore, when many patients become aware of their dependency and loss of functions, they can see themselves as a burden to others, 23,28 and their sense of dignity can be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that in palliative care the sense of dignity was diminished by the loss of physical autonomy, 11,12,14,15,20-22 the dependence and the vulnerability, 5,6,23,24 the loss of internal control over one’s own body 25,26 and the loss of personal worth or values of life leading to loss of meaning in life. 6,27…”
Section: Introductionmentioning
confidence: 99%